2022
DOI: 10.2478/eces-2022-0039
|View full text |Cite
|
Sign up to set email alerts
|

Leaching of Heavy Metals from Contaminated Soil Stabilised by Portland Cement and Slag Bremen

Abstract: Leaching behaviour is an important evidence of soil quality. The assessment of leaching of heavy metals from the contaminated soil is vital for environmental applications. However, leaching may differ in soil stabilised by various ratios of binders. In this study we measured leaching behaviour of soil contaminated by As, Cd, Co, Cr, Cu, Hg, Ni, Pb, V, Zn, methyl Hg, aliphatic compounds of hydrocarbons, polycyclic aromatic hydrocarbons (PAHs), polychlorinated biphenyls (PCBs) and dissolved organic carbon (DOC).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…Aimed at the developing of the unified framework of clayey soil stabilization by blended binders, our study continues the research on improvement its geotechnical properties which has been observed in multiple previous publications [53][54][55][56][57][58][59]. These and other works result from the need of the improved soil properties with the addition of binders in transport infrastructure, which can be achieved by the treatment of soils with stabilising agents.…”
Section: Introductionmentioning
confidence: 60%
See 1 more Smart Citation
“…Aimed at the developing of the unified framework of clayey soil stabilization by blended binders, our study continues the research on improvement its geotechnical properties which has been observed in multiple previous publications [53][54][55][56][57][58][59]. These and other works result from the need of the improved soil properties with the addition of binders in transport infrastructure, which can be achieved by the treatment of soils with stabilising agents.…”
Section: Introductionmentioning
confidence: 60%
“…After collecting and refining the soil samples, the specimens were stored for 90 days. During this curing period, the resonant frequency measurements were performed on the soil specimens using existing methods described earlier as free-free resonate column tests [63][64][65][66][67]. The seismic measurements in this study were performed as evaluation of P-wave velocity after the curing of the soil specimens on day 14.…”
Section: Seismic Measurementsmentioning
confidence: 99%
“…Existing methods of soil remediation used in environmental engineering include the evaluation of leaching potential from soil and immobilization of contaminants [39,40]. Diverse contaminants can be tested, such as toxic heavy metals, (As, Pb, Cd, Cr, Hg, Ni, and Zn) [41][42][43][44], Polycyclic Aromatic Hydrocarbon (PAH) [45], Polychlorinated biphenyl (PCB) [46], and organotin compounds Tributyltin (TBT) [47][48][49][50]. Depending on the approaches, soil leaching may be implemented with or without the renewed leachate [51], and using either dynamic or extraction tests [52].…”
Section: Introductionmentioning
confidence: 99%
“…A popular approach of the environmental engineering evaluation of soil properties includes the common leaching test [53][54][55]. Other examples use the water leach test [56,57], toxicity characteristic leaching [58], column leach test [59,60], or soil layering over the substance drainage system [61].…”
Section: Introductionmentioning
confidence: 99%
“…This is caused by the increased bonds between the soil's particles, which chemically reinforce its inner structure [28][29][30]. Steel slag binds soil particles effectively in contaminated soil polluted by heavy metals, and decreases leaching [31][32][33]. In turn, steel mill sludge can be used for the reinforcement of clay bricks, to decrease negative environmental consequences and to optimise its utilisation [34].…”
Section: Introductionmentioning
confidence: 99%